Comments on Indonesisch-Deutsches Woerterbuch (Kamus Bahasa Indonesia Djerman) by Otto Karow and Irene Hilgers-Hesse - Lopez, Cecilio (The Archive; Vol 2 No 1 (1971): Vol. 2 (New Series), No. 1 (1971), 2024)
Excerpt Even if the user of the IDW is a linguist he will not be sure of the pronunciation of the majority of entries, above all if he has no knowledge of Arabic. A guide to pronunciation, a description of the structure of the Indonesian word, including syllabication, and accentuation are indispensable desiderata. Stems as stems can be recalcitrant to glossing and only in derivations can their value become transparent. The clitics, although numerically few, are of frequent occurrence and should have been more exhaustively treated. There are information which are generally found in the front pages of a dictionary, and in a dictionary like the IDW their absence is to be deplored. Glossing and cross-reference should have been more rigorously observed. A judicious application of Occam’s razor would have eliminated trivialities and ephemera and saved space which could have been utilized for more valuable purposes. On the other hand, I will be very happy to see more full illustrations of colloquial usage and quotations from classical literature if only to satisfy the predominantly practical requirements and the scientific demands as well as add to the completeness of the IDW.